Method for producing olefin polymer
Patent Information
- Application Number
- JP2022034776
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-03-31
- Filing Date
- 2022-03-07
- Publication Date
- 2025-03-13
- Estimated Expiration
- 2042-03-07
AI Technical Summary
Olefin polymerization using a combination of hafnium and zirconium complexes as transition metal catalysts is hindered by zirconium complexes acting as impurities, affecting the physical properties of the resulting polymer and increasing their production amount disproportionately.
Incorporating a specific additive during polymerization to selectively deactivate zirconium complexes, maintaining hafnium complex activity while reducing the production of zirconium-derived polymers.
The method effectively suppresses the production of zirconium-derived polymers, maintaining hafnium complex activity and adjusting the polymer's physical properties.
Smart Images

Figure 00000026_0000 
Figure 00000026_0001
Abstract
Description
[Technical Field]
[0001] The present invention relates to a method for producing an olefin polymer, and more particularly to a method for producing an olefin polymer using a transition metal catalyst. [Background technology]
[0002] In the production of olefin (co)polymers, catalysts comprising a transition metal complex such as a metallocene and a cocatalyst component such as an organoaluminum oxy compound (aluminoxane) are widely used as olefin polymerization catalysts. When olefin polymerization is carried out using such olefin polymerization catalysts, various attempts have been made to adjust the physical properties of the resulting olefin polymer by carrying out the olefin polymerization in the presence of various additives.
[0003] For example, Patent Document 1 discloses that the melting point of the resulting polymer can be lowered by carrying out ethylene polymerization using a supported metallocene catalyst in the presence of an ether or a thioether. The examples in Patent Document 1 specifically show that ethylene / olefin copolymerization was achieved using a supported catalyst containing a zirconium compound or a titanium compound. However, Patent Document 1 does not specifically show polymerization using a supported catalyst containing two or more metallocene compounds, nor polymerization using a supported catalyst containing a hafnium compound.
[0004] In this regard, Patent Document 2 discloses that the melting point of the resulting polymer can be lowered by copolymerizing ethylene with another olefin using a Ziegler-Natta catalyst in the presence of an ether or a thioether.
[0005] Patent Document 3 also discloses a method for producing an olefin polymer, in which an olefin is polymerized in the presence of a supported metallocene catalyst and a specific thioether. The examples in Patent Document 3 specifically show that ethylene / olefin copolymerization was achieved using a supported catalyst containing a zirconium compound. The production method described in Patent Document 3 aims to produce an olefin polymer with high activity and to perform stable polymerization by effectively preventing fouling of the interior of the polymerization vessel, such as the walls and stirring blades. However, Patent Document 3 does not describe the use of a combination of multiple transition metal complexes as a supported metallocene catalyst, nor does it specifically disclose polymerization using a supported catalyst containing a hafnium compound.
[0006] Furthermore, a catalyst for olefin polymerization that combines two transition metal complexes with different properties has also been used. Attempts have also been made to carry out such olefin polymerization in the presence of various additives.
[0007] For example, Patent Document 4 discloses that olefin polymerization using a catalyst comprising a combination of two types of transition metal complexes with different properties is carried out in the presence of a compound having an active proton, such as a polyalkylene oxide block polymer or a higher aliphatic amide. However, Patent Document 4 does not disclose that olefin polymerization is carried out in the presence of an ether in which two hydrocarbon groups are bonded to each other via one oxygen atom, or a thioether in which two hydrocarbon groups are bonded to each other via one sulfur atom. Furthermore, Patent Document 4 does not specifically disclose polymerization using a supported catalyst containing a hafnium compound as a supported metallocene catalyst. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] Special Publication No. 2003-501527 [Patent Document 2] Special Publication No. 2003-501526 [Patent Document 3] Japanese Patent Publication No. 2020-164685 [Patent Document 4] Japanese Patent Application Laid-Open No. 2014-019825 Summary of the Invention [Problem to be solved by the invention]
[0009] Olefin polymerization using an olefin polymerization catalyst comprising a combination of two transition metal complexes with different constituent metals is often actively carried out to adjust the physical properties of the resulting olefin polymer. However, depending on the type of transition metal used, a first transition metal constituting the transition metal complex may contain a second transition metal as an impurity. In this case, olefin polymerization is also carried out using an olefin polymerization catalyst comprising a combination of multiple transition metal complexes with different constituent metals. For example, when a hafnium complex is used as an olefin polymerization catalyst, the olefin polymerization catalyst may contain a zirconium complex as an impurity. In this regard, the present inventors have found that when olefin polymerization is carried out using an olefin polymerization catalyst containing a hafnium complex and a corresponding zirconium complex, (i) the zirconium complex tends to have higher polymerization catalytic activity than the hafnium complex, and (ii) the ratio of the amount of zirconium complex-derived polymer produced to the amount of hafnium complex-derived polymer produced tends to be higher than the ratio of the amount of zirconium complex to the amount of hafnium complex in the olefin polymerization catalyst.
[0010] When an olefin polymer is produced using a hafnium complex, a polymer derived from a zirconium complex contained as an impurity in the hafnium complex may be contaminated, affecting the physical properties of the resulting polymer. Therefore, an object of the present invention is to provide a method for producing an olefin polymer using an olefin polymerization catalyst containing a hafnium complex and a zirconium complex, which can reduce the amount of polymer derived from the zirconium complex produced. [Means for solving the problem]
[0011] The present inventors have discovered that when olefins are polymerized in a catalyst system containing a hafnium complex, the addition of a specific additive to the catalyst system makes it possible to suppress the by-production of a polymer derived from a zirconium complex contained as an impurity in the hafnium complex while maintaining the activity of the hafnium complex to a certain extent, and have completed the present invention. That is, the present invention relates to the following [1] to [9].
[0012] [1] A method for producing an olefin polymer, comprising a step of (co)polymerizing one or more olefins selected from the group consisting of ethylene and α-olefins having 3 to 20 carbon atoms in the presence of an olefin polymerization catalyst comprising the following components (A), (B), and (C): and the following component (D): Component (A): a hafnium compound represented by the following general formula (1);
[0013] [ka]
[0014] [In the general formula (1), n is a number that satisfies the valence of Hf, R 1 ~R 8 each independently represents a hydrogen atom, a hydrocarbon group, a halogen-containing group, an oxygen-containing group, or a nitrogen containing groups, boron containing groups, sulfur containing groups, phosphorus containing groups, silicon containing groups, germanium containing groups and and tin-containing groups, which may be the same or different, R 1 ~R 8 of two adjacent groups may be linked to form a ring, Q 1 is a divalent group, and is a hydrocarbon group having 1 to 20 carbon atoms, a halogen-containing group, a silicon-containing group, a group-containing, germanium-containing or tin-containing group, and The group may contain oxygen; X's each independently represent a hydrogen atom, a halogen atom, a hydrocarbon group, a halogen-containing hydrocarbon group, a group selected from the group consisting of a silicon-containing group, an oxygen-containing group, a sulfur-containing group, a nitrogen-containing group, and a phosphorus-containing group; are atoms or groups that may be the same or different from each other. Component (B): a zirconium compound represented by the following general formula (2);
[0015] [ka]
[0016] [In the general formula (2), n is a number that satisfies the valence of Zr, R 9 ~R 16 are each independently selected from the group consisting of a hydrogen atom, a hydrocarbon group, a halogen-containing group, an oxygen-containing group, a nitrogen-containing group, a boron-containing group, a sulfur-containing group, a phosphorus-containing group, a silicon-containing group, a germanium-containing group, and a tin-containing group, and may be the same or different from each other; R 9 ~R 16 two adjacent groups among these may be linked to form a ring, Q 2 is a divalent group, which is a hydrocarbon group having 1 to 20 carbon atoms, a halogen-containing group, a silicon-containing group, a germanium-containing group, or a tin-containing group, and the hydrocarbon group having 1 to 20 carbon atoms may contain oxygen; X's are each independently an atom or group selected from the group consisting of a hydrogen atom, a halogen atom, a hydrocarbon group, a halogen-containing hydrocarbon group, a silicon-containing group, an oxygen-containing group, a sulfur-containing group, a nitrogen-containing group, and a phosphorus-containing group, and may be the same or different. Component (C): at least one compound selected from the group consisting of an organometallic compound (c-1) represented by the following general formulas (3) to (5), an organoaluminum oxy compound (c-2), and a compound (c-3) that reacts with components (A) and (B) to form an ion pair; R a m Al(OR b ) n H p X q ···(3) [In general formula (3), R a and R b each independently represent a hydrocarbon group having 1 to 15 carbon atoms, X represents a halogen atom, m is a number where 0 < m ≦ 3, n is a number where 0 ≦ n < 3, p is a number where 0 ≦ p < 3, q is a number where 0 ≦ q < 3, and m + n + p + q = 3.] M a AlR a 4···(4) [In general formula (4), M a represents Li, Na or K, and R a represents a hydrocarbon group having 1 to 15 carbon atoms.] R a r M b R b s X t ···(5) [In general formula (5), R a and R b each independently represent a hydrocarbon group having 1 to 15 carbon atoms, M b is selected from Mg, Zn and Cd, X represents a halogen atom, r is a number where 0 < r ≦ 2, s is a number where 0 ≦ s ≦ 1, t is a number where 0 ≦ t ≦ 1, and r + s + t = 2.] Component (D): a compound represented by the following general formula (6); R 17 -E-R 18 ···(6) [In general formula (6), E represents an atom of Group 16 of the periodic table, and R 17 and R 18 each independently represent a hydrocarbon group having from 1 to 20 carbon atoms.]
[0017] [2] 2. The method for producing an olefin polymer according to claim 1, wherein in the general formula (6), E is an oxygen atom or a sulfur atom.
[0018] [3] In the general formula (6), R 17 and R 18 and each independently represent an alkyl group having 1 to 20 carbon atoms.
[0019] [4] In the general formula (6), R 17 and R 18 and each independently represent a linear alkyl group having 1 to 20 carbon atoms.
[0020] [5] In the general formula (6), R 17 and R 18 and are the same linear alkyl groups having 1 to 20 carbon atoms.
[0021] [6] The method for producing an olefin polymer according to any one of [1] to [5], wherein the olefin polymerization catalyst is in a solid state.
[0022] [7] The method for producing an olefin polymer according to [6], wherein the olefin polymerization catalyst further contains a solid support (S).
[0023] [8] The method for producing an olefin polymer according to [7], wherein the component (C) is an organoaluminum oxy compound, and the solid support (S) is a porous oxide.
[0024] [9] The method for producing an olefin polymer according to any one of [1] to [8], wherein the component (A) is a hafnium compound represented by the following general formula (7), and the component (B) is a zirconium compound represented by the following general formula (8):
[0025] [ka]
[0026] [In the general formula (7), n is a number that satisfies the valence of Hf, R 19 ~R 30 are each independently selected from the group consisting of a hydrogen atom, a hydrocarbon group, a halogen-containing group, an oxygen-containing group, a nitrogen-containing group, a boron-containing group, a sulfur-containing group, a phosphorus-containing group, a silicon-containing group, a germanium-containing group, and a tin-containing group, and may be the same or different from each other; R 19 ~R 30 two adjacent groups among these may be linked to form a ring, Q 1 is a divalent group, which is a hydrocarbon group having 1 to 20 carbon atoms, a halogen-containing group, a silicon-containing group, a germanium-containing group, or a tin-containing group, and the hydrocarbon group having 1 to 20 carbon atoms may contain oxygen; X's are each independently an atom or group selected from the group consisting of a hydrogen atom, a halogen atom, a hydrocarbon group, a halogen-containing hydrocarbon group, a silicon-containing group, an oxygen-containing group, a sulfur-containing group, a nitrogen-containing group, and a phosphorus-containing group, and may be the same or different.
[0027] [ka]
[0028] [In the general formula (8), n is a number that satisfies the valence of Zr, R 31 ~R 42are each independently selected from the group consisting of a hydrogen atom, a hydrocarbon group, a halogen-containing group, an oxygen-containing group, a nitrogen-containing group, a boron-containing group, a sulfur-containing group, a phosphorus-containing group, a silicon-containing group, a germanium-containing group, and a tin-containing group, and may be the same or different from each other; R 31 ~R 42 two adjacent groups among these may be linked to form a ring, Q 2 is a divalent group, which is a hydrocarbon group having 1 to 20 carbon atoms, a halogen-containing group, a silicon-containing group, a germanium-containing group, or a tin-containing group, and the hydrocarbon group having 1 to 20 carbon atoms may contain oxygen; X's are each independently an atom or group selected from the group consisting of a hydrogen atom, a halogen atom, a hydrocarbon group, a halogen-containing hydrocarbon group, a silicon-containing group, an oxygen-containing group, a sulfur-containing group, a nitrogen-containing group, and a phosphorus-containing group, and may be the same or different. [Effects of the Invention]
[0029] In the present invention, when an olefin polymer is produced using a hafnium complex, the zirconium complex contained as an impurity in the hafnium complex can be selectively deactivated, thereby reducing the proportion of the polymer derived from the zirconium complex in the resulting polymer. [Brief explanation of the drawings]
[0030] [Figure 1] FIG. 2 is a diagram showing the relationship between the proportion of the polymer derived from component (A) and the proportion of the polymer derived from component (B) obtained by copolymerization and the amount of component (D) added in Examples 1 and 2 and Production Example 3. [Figure 2] FIG. 2 is a diagram showing the relationship between the proportion of the polymer derived from component (A) and the proportion of the polymer derived from component (B) obtained by copolymerization and the amount of component (D) added in Example 3 and Production Example 6. DETAILED DESCRIPTION OF THE INVENTION
[0031] Specific embodiments of the present invention will be described in detail below, but the present invention is not limited to the following embodiments and can be implemented with appropriate modifications within the scope of the object of the present invention.
[0032] In this specification, the terms "polymerization" and "(co)polymerization" are used to encompass both homopolymerization and copolymerization unless otherwise specified. In addition, in this specification, a numerical range expressed using "to" means a range that includes the numerical values written before and after "to" as the lower limit and upper limit.
[0033] [Production method of olefin polymer] The process for producing an olefin polymer according to the present invention comprises a step of (co)polymerizing ethylene and one or more olefins selected from the group consisting of α-olefins having 3 to 20 carbon atoms in the presence of an olefin polymerization catalyst described below and component (D) described below. This (co)polymerization is usually carried out in a polymerization vessel. The production method according to the present invention will be described in detail below.
[0034] <Olefin polymerization catalyst> The production method of the present invention uses an olefin polymerization catalyst comprising the following components (A), (B), and (C). This olefin polymerization catalyst is preferably solid. Furthermore, this olefin polymerization catalyst may contain a solid support (S) in addition to components (A), (B), and (C), and may also contain component (G). Each component used in the olefin polymerization catalyst will now be described.
[0035] Component (A) In the present invention, a hafnium complex is used as component (A) constituting the olefin polymerization catalyst. Component (A) used in the present invention is specifically a hafnium compound represented by the following general formula (1):
[0036] [ka]
[0037] In the general formula (1), n is a number that satisfies the valence of Hf, specifically an integer of 1 to 4, and preferably 2. R 1 ~R 8 are each independently selected from the group consisting of a hydrogen atom, a hydrocarbon group, a halogen-containing group, an oxygen-containing group, a nitrogen-containing group, a boron-containing group, a sulfur-containing group, a phosphorus-containing group, a silicon-containing group, a germanium-containing group, and a tin-containing group, and may be the same or different from each other.
[0038] Examples of the hydrocarbon group include alkyl groups, cycloalkyl groups, alkenyl groups, aryl groups, and arylalkyl groups. Examples of alkyl groups include methyl groups, ethyl groups, n-propyl groups, isopropyl groups, n-butyl groups, isobutyl groups, s-butyl groups, t-butyl groups, n-pentyl groups, neopentyl groups, n-hexyl groups, n-octyl groups, nonyl groups, dodecyl groups, and eicosyl groups. Examples of cycloalkyl groups include cyclopropyl groups, cyclobutyl groups, cyclopentyl groups, cyclohexyl groups, norbornyl groups, and adamantyl groups. Examples of alkenyl groups include vinyl groups, propenyl groups, and cyclohexenyl groups. Examples of aryl groups include phenyl, tolyl, dimethylphenyl, trimethylphenyl, ethylphenyl, propylphenyl, α- or β-naphthyl, methylnaphthyl, anthracenyl, phenanthryl, benzylphenyl, pyrenyl, acenaphthyl, phenalenyl, aceanthryllenyl, tetrahydronaphthyl, indanyl, and biphenylyl. Examples of arylalkyl groups include benzyl, phenylethyl, and phenylpropyl.
[0039] Examples of the silicon-containing group include alkylsilyl groups such as a methylsilyl group, a dimethylsilyl group, a trimethylsilyl group, an ethylsilyl group, a diethylsilyl group, a triethylsilyl group, and a dimethyl-tert-butylsilyl group; and arylsilyl groups such as a dimethylphenylsilyl group, a diphenylmethylsilyl group, and a triphenylsilyl group.
[0040] R 1 ~R 8 Two adjacent groups among R may be linked to form a ring. 5 and R 6 , and ,R 7 and R 8 are linked to each other to form a ring.
[0041] Q 1 is a divalent group, which is a hydrocarbon group having 1 to 20 carbon atoms, a halogen-containing group, a silicon-containing group, a germanium-containing group, or a tin-containing group, and the hydrocarbon group having 1 to 20 carbon atoms may contain oxygen.
[0042] Q 1 Examples of the hydrocarbon group having 1 to 20 carbon atoms which may contain oxygen include alkylidene groups having 1 to 20 carbon atoms such as a methylene group, a 1,2-ethylidene group, a 1,2-ethylidene group, and an isopropylidene group; methylene groups having 13 to 20 carbon atoms and having two or more aryl groups such as a diphenylmethylene group and a di(p-tolyl)methylene group; and di(alkoxyphenyl)methylene groups having 15 to 20 carbon atoms such as a di(p-methoxyphenyl)methylene group.
[0043] Q 1Examples of silicon-containing groups that can be the above include silylene, methylsilylene, dimethylsilylene, diisopropylsilylene, dibutylsilylene, methylbutylsilylene, methyl-t-butylsilylene, dicyclohexylsilylene, methylcyclohexylsilylene, methylphenylsilylene, diphenylsilylene, ditolylsilylene, methylnaphthylsilylene, dinaphthylsilylene, cyclodimethylenesilylene, cyclotrimethylenesilylene, cyclotetramethylenesilylene, cyclopentamethylenesilylene, cyclohexamethylenesilylene, and cycloheptamethylenesilylene, and particularly preferred are dialkylsilylene groups such as dimethylsilylene and dibutylsilylene.
[0044] In one particularly preferred embodiment of the present invention, Q 1 is a di(p-methoxyphenyl)methylene group. In another particularly preferred embodiment of the present invention, Q 1 is a di(p-tolyl)methylene group. Each X is independently an atom or group selected from the group consisting of a hydrogen atom, a halogen atom, a hydrocarbon group, a halogen-containing hydrocarbon group, a silicon-containing group, an oxygen-containing group, a sulfur-containing group, a nitrogen-containing group, and a phosphorus-containing group, and is preferably a halogen atom or a hydrocarbon group. Examples of halogen atoms include fluorine, chlorine, bromine, and iodine, and chlorine is particularly preferred. When n is 2 or more, the multiple groups represented by X may be the same or different. When there are multiple groups represented by X, the multiple Xs may be bonded to each other to form a ring.
[0045] In a preferred exemplary embodiment of the present invention, the component (A) used in the present invention is a hafnium compound represented by the following general formula (7).
[0046] [ka]
[0047] In the general formula (7), n is the same as n in the general formula (1). R 19 ~R 30 are each independently selected from the group consisting of a hydrogen atom, a hydrocarbon group, a halogen-containing group, an oxygen-containing group, a nitrogen-containing group, a boron-containing group, a sulfur-containing group, a phosphorus-containing group, a silicon-containing group, a germanium-containing group, and a tin-containing group, and may be the same or different. 19 ~R 30 Examples of the hydrocarbon group and silicon-containing group that can be 1 ~R 8 The same applies to the hydrocarbon group and silicon-containing group which can be the same.
[0048] R 19 ~R 30 Two adjacent groups among R may be linked to form a ring. 24 and R 25 , and ,R 28 and R 29 are linked to each other to form a ring.
[0049] Q 1 and X are each the Q in the general formula (1). 1 and X. In one particularly preferred embodiment of the present invention, the component (A) used in the present invention is a hafnium compound represented by the following general formula (9).
[0050] [ka]
[0051] In the general formula (9), n and Q 1 and X are respectively n and Q in the above general formula (1). 1 and X. In another particularly preferred embodiment of the present invention, the component (A) used in the present invention is a hafnium compound represented by the following general formula (11). [ka]
[0052] In the general formula (11), n and Q 1 and X are respectively n and Q in the above general formula (1). 1 and X.
[0053] Ingredient (B) In the present invention, component (B) constituting the olefin polymerization catalyst is a zirconium complex. Specifically, component (B) used in the present invention is a zirconium compound represented by the following general formula (2):
[0054] [ka]
[0055] In the general formula (2), n is a number that satisfies the valence of Zr, specifically an integer of 1 to 4, and preferably 2. R 9 ~R 16 are each independently selected from the group consisting of a hydrogen atom, a hydrocarbon group, a halogen-containing group, an oxygen-containing group, a nitrogen-containing group, a boron-containing group, a sulfur-containing group, a phosphorus-containing group, a silicon-containing group, a germanium-containing group, and a tin-containing group, and may be the same or different. 9 ~R 16 Examples of the hydrocarbon group and silicon-containing group that can be 1 ~R 8 The same applies to the hydrocarbon group and silicon-containing group which can be the same.
[0056] R 9 ~R 16 Two adjacent groups among R may be linked to form a ring. 13 and R 14 , and ,R 15 and R 16 are linked to each other to form a ring.
[0057] Q 2is a divalent group, and is a hydrocarbon group having 1 to 20 carbon atoms, a halogen-containing group, a silicon-containing group, a germanium-containing group, or a tin-containing group, and the hydrocarbon group having 1 to 20 carbon atoms may contain oxygen. 2 Examples of the hydrocarbon group having 1 to 20 carbon atoms and the silicon-containing group that can be Q in the general formula (1) are 1 The same applies to the hydrocarbon group and silicon-containing group which can be the same.
[0058] Each X is independently an atom or group selected from the group consisting of a hydrogen atom, a halogen atom, a hydrocarbon group, a halogen-containing hydrocarbon group, a silicon-containing group, an oxygen-containing group, a sulfur-containing group, a nitrogen-containing group, and a phosphorus-containing group, and is preferably a halogen atom or a hydrocarbon group. Examples of halogen atoms include fluorine, chlorine, bromine, and iodine, and chlorine is particularly preferred. When n is 2 or more, the multiple groups represented by X may be the same or different. When there are multiple groups represented by X, the multiple Xs may be bonded to each other to form a ring.
[0059] In a preferred exemplary embodiment of the present invention, the component (B) used in the present invention is a zirconium compound represented by the following general formula (8).
[0060] [ka]
[0061] In the general formula (8), n is the same as n in the general formula (2). R 19 ~R 30 are each independently selected from the group consisting of a hydrogen atom, a hydrocarbon group, a halogen-containing group, an oxygen-containing group, a nitrogen-containing group, a boron-containing group, a sulfur-containing group, a phosphorus-containing group, a silicon-containing group, a germanium-containing group, and a tin-containing group, and may be the same or different. 19 ~R 30 Examples of the hydrocarbon group and silicon-containing group that can be 1 ~R 8The same applies to the hydrocarbon group and silicon-containing group which can be the same.
[0062] R 19 ~R 30 Two adjacent groups among R may be linked to form a ring. 24 and R 25 , and ,R 28 and R 29 are linked to each other to form a ring.
[0063] Q 2 and X are each the Q in the above general formula (2). 2 and X. In one particularly preferred embodiment of the present invention, the component (B) used in the present invention is a zirconium compound represented by the following general formula (10).
[0064] [ka]
[0065] In the general formula (10), n and Q 2 and X are respectively n and Q in the above general formula (2). 2 and X. In another particularly preferred embodiment of the present invention, the component (B) used in the present invention is a zirconium compound represented by the following general formula (12). [ka]
[0066] In the general formula (12), n and Q 2 and X are respectively n and Q in the above general formula (2). 2 and X. In one typical embodiment of the present invention, the production method of the present invention is carried out when producing an olefin polymer using a hafnium catalyst containing the above-mentioned component (B) as an impurity in addition to the above-mentioned component (A). In this embodiment, the ligand constituting the above-mentioned component (B) is often the same as the ligand constituting the above-mentioned component (A). Therefore, in one exemplary embodiment of the present invention, R 9 ~R 16 , n, Q 2 and X are R in the above general formula (1), respectively. 1 ~R 8 , n, Q 1 and X are the same as those in the general formula (2). 9 ~R 16 , n, Q 2 and X are not necessarily all R in the general formula (1). 1 ~R 8 , n, Q 1 and X do not have to be the same as, for example, R in the above general formula (2) 9 ~R 16 , n, Q 2 and X are each R in the general formula (1). 1 ~R 8 , n, Q 1 and X may be different from each other. The same applies to R in general formula (8). 31 ~R 42 , n, Q 2 and X and R in the above general formula (7) 19 ~R 30 , n, Q 1 and the relationship with X, n and Q in the general formula (10) 2 and X and n and Q in the above general formula (9) 1 and X, and n, Q in the general formula (12) 2 and X and n and Q in the above general formula (11) 1 and also in relation to X.
[0067] Ingredients (C) In addition to the above components (A) and (B), the olefin polymerization catalyst used in the present invention uses a specific organoaluminum compound as component (C). This component (C) functions as a cocatalyst. Specifically, it is at least one compound selected from the group consisting of an organometallic compound (c-1) represented by the following general formulas (3) to (5), an organoaluminum oxy compound (c-2), and a compound (c-3) that reacts with components (A) and (B) to form an ion pair; R a m Al(OR b ) n H p X q ···(3) [In general formula (3), R a and R b each independently represent a hydrocarbon group having 1 to 15 carbon atoms, X represents a halogen atom, m is a number where 0 < m ≦ 3, n is a number where 0 ≦ n < 3, p is a number where 0 ≦ p < 3, q is a number where 0 ≦ q < 3, and m + n + p + q = 3.] M a AlR a 4···(4) [In general formula (4), M a represents Li, Na or K, and R a represents a hydrocarbon group having 1 to 15 carbon atoms.] R a r M b [[ID=第38]]R b s X t ···(5) [In general formula (5), R a [[ID=第47]]and R b each independently represent a hydrocarbon group having 1 to 15 carbon atoms, M b is selected from Mg, Zn and Cd, X represents a halogen atom, r is a number where 0 < r ≦ 2, s is a number where 0 ≦ s ≦ 1, t is a number where 0 ≦ t ≦ 1, and r + s + t = 2.] Among the organometallic compounds (c-1) represented by general formula (3), (4), or (5), those represented by general formula (3) are preferred, and specific examples include trialkylaluminums such as trimethylaluminum, triethylaluminum, triisopropylaluminum, triisobutylaluminum, trihexylaluminum, and trioctylaluminum; and alkylaluminum hydrides such as dimethylaluminum hydride, diethylaluminum hydride, diisopropylaluminum hydride, di-n-butylaluminum hydride, diisobutylaluminum hydride, and diisohexylaluminum hydride. These may be used alone or in combination of two or more.
[0068] As the organoaluminum oxy compound (c-2), an organoaluminum oxy compound prepared from trialkylaluminum or tricycloalkylaluminum is preferred, and an aluminoxane prepared from trimethylaluminum or triisobutylaluminum is particularly preferred. Such organoaluminum oxy compounds may be used alone or in combination of two or more.
[0069] As the compound (c-3) that reacts with component (A) and component (B) to form an ion pair, Lewis acids, ionic compounds, borane compounds, carborane compounds, and heteropoly compounds and isopoly compounds described in, for example, JP-T-1-501950, JP-T-1-502036, JP-A-3-179005, JP-A-3-179006, JP-A-3-207703, JP-A-3-207704, and U.S. Pat. No. 5,321,106 can be used without limitation. In the present invention, the component (C) is preferably the organoaluminum oxy compound (c-2).
[0070] Solid carrier (S) The olefin polymerization catalyst used in the present invention may further contain a solid support (S) in addition to the components (A), (B), and (C). In a preferred embodiment of the present invention, the olefin polymerization catalyst further contains a solid support (S). The solid support (S) that can be used in the present invention is an inorganic or organic compound, and is a granular or fine particle solid.
[0071] Among these, examples of inorganic compounds include porous oxides, inorganic chlorides, clays, clay minerals, and ion-exchange layered compounds, and preferably porous oxides. Porous oxides that can be used include SiO2, Al2O3, MgO, ZrO, TiO2, B2O3, CaO, ZnO, BaO, and ThO2, as well as composites or mixtures containing these, specifically natural or synthetic zeolites, SiO2-MgO, SiO2-Al2O3, SiO2-TiO2, SiO2-V2O5, SiO2-Cr2O3, and SiO2-TiO2-MgO. Of these, those containing SiO2 as the main component are preferred.
[0072] The properties of such porous oxides vary depending on the type and production method, but the solid support used in the present invention has a particle size of usually 0.2 to 300 μm, preferably 1 to 200 μm, and a specific surface area of usually 50 to 1200 m 2 / g, preferably 100 to 1000m 2 / g, and the pore volume is typically 0.3 to 30 cm 3 / g range. Such a carrier is calcined, for example, at 100 to 1000°C, preferably 150 to 700°C, as needed, before use. In the present invention, the solid support (S) is preferably the porous oxide.
[0073] Ingredients (G) The olefin polymerization catalyst used in the present invention may further contain a polyalkylene oxide alkyl ether as component (G), in addition to the above-mentioned components (A), (B), and (C) and the optional solid support (S).
[0074] In the present invention, such component (G) can be present in the olefin polymerization catalyst for the purpose of suppressing fouling in the reactor or improving the particle properties of the produced polymer. An example of the polyalkylene oxide alkyl ether is polyoxyethylene lauryl ether.
[0075] Method for producing an olefin polymerization catalyst A method for preparing the olefin polymerization catalyst used in the present invention will now be described. The olefin polymerization catalyst used in the present invention can be prepared by adding the above-mentioned components (A), (B) and (C) to an inert hydrocarbon or to a polymerization system using an inert hydrocarbon.
[0076] The order of addition of the components is arbitrary, but a preferred order is, for example, i) A method in which component (A) and component (B) are mixed and contacted, and then component (C) is contacted and added to the polymerization system. ii) A method in which a contact product obtained by mixing and contacting component (A) with component (C) and a contact product obtained by mixing and contacting component (B) with component (C) are added to a polymerization system. iii) A method in which components (A), (B) and (C) are each continuously added to the polymerization system.
[0077] When the olefin polymerization catalyst contains a solid support (S), the solid catalyst component (X) can be prepared by contacting at least one of the components (A), (B) and (C) with the solid support (S) in an inert hydrocarbon. The order of contacting the components is arbitrary, but a preferred order is, for example, iv) A method of preparing a solid catalyst component (X) by contacting the component (C) with a solid support (S) and then contacting the component (A) with the component (B). v) A method of mixing and contacting component (A), component (B) and component (C) and then contacting the mixture with a solid carrier (S). vi) A method using a solid catalyst component (X1) prepared by contacting the component (C) with a solid support (S) and then with the component (A), and a solid catalyst component (X2) prepared by contacting the component (C) with a solid support (S) and then with the component (B), etc., and iv) is more preferred.
[0078] When the olefin polymerization catalyst also contains component (G), component (G) may be present in any step in the preparation of the olefin polymerization catalyst, and the order of contact is also arbitrary. For example, when the contacting order of the components is as described in iv) above, component (G) can be added after the contacting of components (A) and (B).
[0079] Specific examples of inert hydrocarbons include aliphatic hydrocarbons such as propane, butane, pentane, hexane, heptane, octane, decane, dodecane, and kerosene; alicyclic hydrocarbons such as cyclopentane, cyclohexane, and methylcyclopentane; aromatic hydrocarbons such as benzene, toluene, and xylene; and halogenated hydrocarbons such as ethylene chloride, chlorobenzene, and dichloromethane, or mixtures thereof.
[0080] The contact time between component (C) and solid support (S) is usually 0 to 20 hours, preferably 0 to 10 hours, and the contact temperature is usually −50 to 200° C., preferably −20 to 120° C. The molar ratio of component (C) to solid support (S) (component (C) / solid support (S)) at the time of contact is usually 0.2 to 2.0, particularly preferably 0.4 to 2.0.
[0081] The contact time of the contact product of component (C) and solid support (S) with component (A) and component (B) is usually 0 to 5 hours, preferably 0 to 2 hours, and the contact temperature is usually -50 to 200°C, preferably -50 to 100°C. The amount of contact between component (A) and component (B) largely depends on the type and amount of component (C). When component (c-1) is used, it is used in an amount such that the molar ratio of component (c-1) to the total transition metal atoms (M) in components (A) and (B) [(c-1) / M] is usually 0.01 to 100,000, preferably 0.05 to 50,000. When component (c-2) is used, it is used in an amount such that the molar ratio of aluminum atoms in component (c-2) to the total transition metal atoms (M) in components (A) and (B) [(c-2) / M] is usually 10 to 500,000, preferably 20 to 100,000. When component (c-3) is used, it is used in an amount such that the molar ratio of component (c-3) to the total transition metal atoms (M) in components (A) and (B) [(c-3) / M] is usually 1 to 10, preferably 1 to 5. The ratio of component (C) to the total transition metal atoms (M) in components (A) and (B) is determined by inductively coupled plasma (ICP) emission spectroscopy.
[0082] The ratio of the amounts of component (A) and component (B) used can be determined arbitrarily based on the molecular weight and molecular weight distribution of the olefin polymer. The molar ratio of component (A) relative to the total of component (A) and component (B), 100%, is typically 40 to 99.9%. In a typical embodiment of the present invention, the production method of the present invention is carried out in a state where the amount of component (A) is sufficiently greater than the amount of component (B). In such an embodiment, the molar ratio is preferably 80 to 99.9%, more preferably 90 to 99.9%. However, depending on the conditions under which the production method of the present invention is carried out, the production method of the present invention may be carried out in a state where the amounts of component (A) and component (B) are equal or nearly equal; for example, the molar ratio may be 40 to 60%.
[0083] The olefin polymerization catalyst may be a prepolymerization catalyst component obtained by prepolymerizing an olefin. The prepolymerization catalyst component is formed from an olefin polymerization catalyst and, if necessary, an olefin polymer produced by prepolymerization. The prepolymerization catalyst contains the components (A), (B), and (C), an optional solid support (S), and an optional component (G), and, if necessary, an olefin polymer produced by prepolymerization. A method for preparing the prepolymerization catalyst includes, for example, a method in which a small amount of olefin is prepolymerized in a solid catalyst component obtained by contact according to any one of the above i) to vi). Specific examples of the inert hydrocarbon solvent used in preparing the prepolymerization catalyst include the same inert hydrocarbons as those mentioned above.
[0084] The olefin used in the prepolymerization desirably contains in the range of 100 to 0 mol% ethylene, 0 to 49 mol% propylene, and 0 to 100 mol% of an olefin having 4 or more carbon atoms, preferably in the range of 100 to 0 mol% ethylene, 0 to 20 mol% propylene, and 0 to 100 mol% of an olefin having 4 or more carbon atoms, more preferably in the range of 100 to 20 mol% ethylene, 0 to 20 mol% propylene, and 0 to 80 mol% of an olefin having 4 or more carbon atoms, and particularly preferably in the range of 100 to 20 mol% ethylene and 0 to 80 mol% of an olefin having 4 or more carbon atoms.
[0085] Specific examples of olefins having 4 or more carbon atoms include α-olefins having 4 to 20 carbon atoms, such as 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, and 1-eicosene. Additionally, cyclopentene, cycloheptene, norbornene, 5-methyl-2-norbornene, tetracyclododecene, 2-methyl-1,4,5,8-dimethano-1,2,3,4,4a,5,8,8a-octahydronaphthalene, styrene, vinylcyclohexane, and dienes can also be used.
[0086] In preparing the prepolymerization catalyst, components (A) and (B) are each used in an amount of usually 0.001 to 1.0 mmol, preferably 0.005 to 0.5 mmol, per gram of solid support (S), and component (C) is used in an amount of usually 0.1 to 100 mmol, preferably 0.5 to 20 mmol, calculated as the metal atom contained in component (C).
[0087] The prepolymerization catalyst obtained as described above desirably supports components (A) and (B) in amounts of 0.005 to 1.0 mmol, and preferably 0.01 to 0.3 mmol, per gram of solid support (S); supports component (C) in an amount of about 1.0 to 100 mmol, and preferably 2.0 to 50 mmol, calculated as the metal atom contained in component (C); and supports the olefin polymer produced by prepolymerization in an amount of about 0.1 to 500 g, preferably 0.3 to 300 g, and particularly preferably 1 to 100 g, per gram of solid support (S).
[0088] <Ingredient (D)> When one or more olefins selected from the group consisting of ethylene and α-olefins having 3 to 20 carbon atoms are (co)polymerized using the olefin polymerization catalyst containing the components (A) and (B), the resulting polymer includes a polymer produced by a catalytic reaction with the component (A) (herein referred to as a "component (A)-derived polymer") and a polymer produced by a catalytic reaction with the component (B) (herein referred to as a "component (B)-derived polymer"). In such (co)polymerizations, the component (B) tends to have higher polymerization catalytic activity than the component (A), and the ratio of the amount of the component (A)-derived polymer produced to the amount of the component (B)-derived polymer produced tends to be higher than the ratio of the amount of the component (B) to the amount of the component (A) in the olefin polymerization catalyst. In the production method of the present invention, by carrying out this (co)polymerization in the presence of a specific additive, the production of the component (B)-derived polymer can be suppressed while maintaining the production amount of the component (A)-derived polymer to a certain extent. The quantitative ratio of the polymer derived from component (A) to the polymer derived from component (B) in the obtained polymer can be determined by the method described in "Method for measuring the quantitative ratio of the polymer derived from component (A) to the polymer derived from component (B)" in the examples below.
[0089] In the present invention, such an additive is used as component (D). Component (D) is specifically a compound represented by the following general formula (6): R 17 -ER 18 ···(6) [In the general formula (6), E represents an atom of Group 16 of the periodic table, and R 17 and R 18 each independently represents a hydrocarbon group having 1 to 20 carbon atoms. The present inventors speculate that the effect of suppressing the production of the component (B)-derived polymer while maintaining the production amount of the component (A)-derived polymer to a certain extent is achieved by component (D) selectively reducing the catalytic activity of component (B) while maintaining the catalytic activity of component (A).
[0090] Here, in the formula (6), E is preferably an oxygen atom or a sulfur atom. R 17 and R 18 The hydrocarbon group constituting R may be saturated or unsaturated, aliphatic or aromatic, and may be linear, branched, or cyclic. For example, any of aliphatic hydrocarbon groups such as alkyl groups and alkenyl groups, and aromatic hydrocarbon groups may be used. 17 and R 18 are each independently preferably an alkyl group having 1 to 20 carbon atoms, more preferably a linear alkyl group having 1 to 20 carbon atoms.
[0091] Here, the R 17 and R 18 may be the same or different from each other. 17 and R 18 are preferably the same, and more preferably the same linear alkyl group having 1 to 20 carbon atoms.
[0092] Preferred specific examples of the compound represented by the general formula (6) include dibutyl ether, dioctyl ether, dicetyl ether, dibutyl sulfide, dicetyl sulfide, etc., with dibutyl ether being particularly preferred.
[0093] The amount of component (D) used is preferably 1 to 500 ppm, more preferably 1 to 300 ppm, and particularly preferably 3 to 100 ppm, based on the amount of the resulting olefin polymer.
[0094] <Method of producing olefin polymer> The method for producing an olefin polymer according to the present invention comprises a step of (co)polymerizing one or more olefins selected from the group consisting of ethylene and α-olefins having 3 to 20 carbon atoms in the presence of the olefin polymerization catalyst and the component (D).
[0095] Polymerization can be carried out in suspension, solution, or gas phase, and is particularly preferably carried out in suspension or gas phase by slurry polymerization or gas phase polymerization. Specific examples of inert hydrocarbon media used in slurry polymerization include aliphatic hydrocarbons such as propane, butane, pentane, hexane, heptane, octane, decane, dodecane, and kerosene; alicyclic hydrocarbons such as cyclopentane, cyclohexane, and methylcyclopentane; aromatic hydrocarbons such as benzene, toluene, and xylene; halogenated hydrocarbons such as ethylene chloride, chlorobenzene, and dichloromethane, and mixtures thereof. Among these, aliphatic hydrocarbons and alicyclic hydrocarbons are preferred. Alternatively, the olefin itself can be used as the solvent.
[0096] The polymerization temperature is usually -50 to 150°C, preferably 0 to 100°C, in the case of slurry polymerization, and usually 0 to 120°C, preferably 20 to 100°C, in the case of gas phase polymerization. The polymerization pressure is usually atmospheric pressure to 10 MPa gauge pressure, preferably atmospheric pressure to 5 MPa gauge pressure. The polymerization reaction can be carried out by any of batch, semi-continuous, and continuous methods.
[0097] The polymerization can be carried out in two or more stages with different reaction conditions. The molecular weight of the resulting olefin polymer can also be adjusted by adding hydrogen to the polymerization system or by changing the polymerization temperature.
[0098] Specific examples of ethylene and α-olefins having 3 to 20 carbon atoms include ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, and 1-eicosene. These can be used alone or in combination. Furthermore, other copolymerizable monomers may be used in addition to ethylene and α-olefins having 3 to 20 carbon atoms. Examples of copolymerizable monomers include cyclopentene, cycloheptene, norbornene, 5-methyl-2-norbornene, tetracyclododecene, and 2-methyl-1,4,5,8-dimethano-1,2,3,4,4a,5,8,8a-octahydronaphthalene. Furthermore, styrene, vinylcyclohexane, and dienes can also be used.
[0099] As the olefin, it is preferable to use ethylene alone or ethylene and an α-olefin having 3 to 20 carbon atoms. In particular, it is preferable to use 100 to 0 mol% ethylene, 0 to 49 mol% propylene, and 0 to 100 mol% of an olefin having 4 or more carbon atoms. It is more preferable to use 100 to 0 mol% ethylene, 0 to 20 mol% propylene, and 0 to 100 mol% of an α-olefin having 4 or more carbon atoms. It is particularly preferable to use 100 to 20 mol% ethylene, 0 to 20 mol% propylene, and 0 to 80 mol% of an α-olefin having 4 or more carbon atoms. It is most preferable to use 100 to 20 mol% ethylene and 0 to 80 mol% of an α-olefin having 4 or more carbon atoms. Furthermore, in the present invention, it is preferable to produce an ethylene-based polymer using ethylene as the main monomer. As the ethylene-based polymer, a (co)polymer containing 50 mol% or more of an ethylene component and, if necessary, an α-olefin component having 4 to 10 carbon atoms is preferred.
[0100] In polymerization, the components (A) and (B) constituting the olefin polymerization catalyst are each converted into the total of transition metal atoms in the components (A) and (B) and are usually 10 -8 ~10 -3 moles, preferably 10 -7 ~10 -4 Component (C) is preferably used in an amount of usually 10 to 500 mol, and preferably 20 to 200 mol, per mol of transition metal atoms in components (A) and (B) calculated as metal atoms contained in component (C).
[0101] The component (D) is preferably used in an amount of 1 ppm by mass or more relative to the yield of the olefin polymer, since the effect of adjusting the MFR of the resulting olefin polymer tends to be sufficiently exhibited. On the other hand, the component (D) is preferably used in an amount of 500 ppm by mass or less, since this tends to suppress an increase in the load on recovery and purification of the polymerization solvent and gas and a decrease in catalyst performance. The amount of the component (D) used is more preferably 1 ppm by mass or more and 300 ppm by mass or less, particularly preferably 3 ppm by mass or more and 100 ppm by mass or less. [Example]
[0102] The present invention will be explained in more detail below based on examples, but the present invention is not limited to these examples in any way.
[0103] [Synthesis of Components (A) and (B)] <Synthesis Example 1> [bis(4-methoxyphenyl)methylene (η 5 -cyclopentadienyl)(η 5 [-tetramethyloctahydrodibenzofluorenyl)]hafnium dichloride (hereinafter also referred to as “component (A-1)”) was synthesized based on the method described in WO2015 / 122414.
[0104] [ka]
[0105] <Synthesis Example 2> [Bis(4-methoxyphenyl)methylene(η5-cyclopentadienyl)(η5-tetramethyloctahydrodibenzofluorenyl)]zirconium dichloride (hereinafter also referred to as "component (B-1)") represented by the following formula (B-1) was synthesized in the same manner as in Synthesis Example 1 above, except that hafnium tetrachloride was changed to zirconium tetrachloride.
[0106] [ka]
[0107] <Synthesis Example 3> [Di(p-tolyl)methylene (η 5 -cyclopentadienyl)(η 5 -octamethyloctahydrodibenzofluorenyl)]hafnium dichloride (hereinafter also referred to as "component (A-2)") is a compound of [di(p-tolyl)methylene(η 5 -cyclopentadienyl)(η 5 -octamethyloctahydrodibenzofluorenyl)]zirconium dichloride synthesis method described in JP 2008-231266, except that zirconium tetrachloride was changed to hafnium tetrachloride. 5 -cyclopentadienyl)(η 5 -octamethyloctahydrodibenzofluorenyl)]zirconium dichloride was synthesized in the same manner as in the synthesis of benzoyl zirconium dichloride. [ka]
[0108] <Synthesis Example 4> [Di(p-tolyl)methylene (η 5 -cyclopentadienyl)(η 5-octamethyloctahydrodibenzofluorenyl)]zirconium dichloride (hereinafter also referred to as "component (B-2)") was synthesized based on the method described in JP 2008-231266 A. [ka]
[0109] [Synthesis of solid catalyst component (X)] <Synthesis Example 5> In a 270 L reactor equipped with a stirrer, silica (average particle size 70 μm, specific surface area 340 m) manufactured by Fuji Silysia Ltd. was used as a solid carrier (S) under a nitrogen atmosphere. 2 / g, pore volume 1.3cm 3 10 kg of methylaluminoxane (3.5 mol / L in terms of Al atoms, calcined at 250°C) was suspended in 77 L of toluene and then cooled to 0-5°C. 20.4 L of a toluene solution of methylaluminoxane (component (C)) (3.5 mol / L in terms of Al atoms) was added dropwise to this suspension over 30 minutes. The temperature of the system was maintained at 0-5°C. After the reaction was continued at 0-5°C for 30 minutes, the temperature was raised to 95-100°C over approximately 1.5 hours and then continued at 95-100°C for 4 hours. The temperature was then lowered to room temperature, the supernatant liquid was removed by decantation, and the mixture was washed twice with toluene to prepare a toluene slurry with a total volume of 58.0 L. A portion of the resulting slurry component was sampled and its concentration was examined; the slurry concentration was 248.0 g / L and the Al concentration was 1.21 mol / L.
[0110] Next, 12.6 mL of toluene and 0.6 mL (0.60 mL) of the slurry obtained above were placed in a 20 mL Schlenk tube that had been thoroughly purged with nitrogen. 1.8 mL (1.82 mL) of a 2 mM toluene solution of component (A-1) obtained in Synthesis Example 1 was added, and the mixture was allowed to contact with the mixture at a system temperature of 20 to 25°C for 1 hour to obtain a toluene slurry of solid catalyst component (X-1).
[0111] <Synthesis Example 6> A toluene slurry of solid catalyst component (X-2) was obtained in the same manner as in Synthesis Example 3, except that (B-1) was used instead of component (A-1) in Synthesis Example 5.
[0112] <Synthesis Example 7> A toluene slurry of solid catalyst component (X-3) was obtained in the same manner as in Synthesis Example 5, except that the amount of the 2 mM toluene solution of component (A-1) added was changed to 0.9 mL (0.91 mL) and 0.9 mL (0.91 mL) of the 2 mM toluene solution of (B-1) was added after the addition of the toluene solution of component (A-1).
[0113] <Synthesis Example 8> A toluene slurry of solid catalyst component (X-4) was obtained in the same manner as in Synthesis Example 5, except that component (A-2) was used instead of component (A-1).
[0114] <Synthesis Example 9> A toluene slurry of solid catalyst component (X-5) was obtained in the same manner as in Synthesis Example 5, except that component (B-2) was used instead of component (A-1).
[0115] <Synthesis Example 10> A toluene slurry of solid catalyst component (X-6) was obtained in the same manner as in Synthesis Example 5, except that in Synthesis Example 5, 1.64 mL of a 2 mM toluene solution of component (A-2) was added instead of 1.82 mL of a 2 mM toluene solution of component (A-1), and 0.18 mL of a 2 mM toluene solution of (B-2) was added after the addition of the toluene solution of component (A-2).
[0116] [Manufacturing Example 1] A 1 L stainless steel autoclave equipped with a stirring blade and thoroughly purged with nitrogen was charged with 500 mL of heptane under a nitrogen atmosphere, and then ethylene was passed through to saturate the liquid and gas phases with ethylene. Next, 0.150 mmol of triisobutylaluminum and 5.0 mL of a toluene slurry of the solid catalyst component (X-1) were added, and the temperature and pressure were raised to 80°C and 0.8 MPaG using ethylene gas, and polymerization was carried out for 90 minutes. The resulting polymer was filtered and vacuum dried at 80°C for 10 hours, yielding 15.74 g of polyethylene.
[0117] [Manufacturing Example 2] The same procedure as in Production Example 1 was repeated except that 5.0 mL of a toluene slurry of the solid catalyst component (X-2) was used instead of the toluene slurry of the solid catalyst component (X-1), to obtain 9.42 g of polyethylene.
[0118] [Manufacturing Example 3] The same procedure as in Production Example 1 was carried out except that 5.0 mL of a toluene slurry of the solid catalyst component (X-3) was used instead of the toluene slurry of the solid catalyst component (X-1), to obtain 50.92 g of polyethylene.
[0119] [Manufacturing Example 4] A 1-L stainless steel autoclave equipped with a stirring blade and thoroughly purged with nitrogen was charged with 500 mL of heptane under a nitrogen atmosphere. Ethylene was then passed through the autoclave to saturate the liquid and gas phases with ethylene. Next, 1.0 mL of 1-hexene, 0.150 mmol of triisobutylaluminum, and 5.0 mL of a toluene slurry of the solid catalyst component (X-4) were added. The temperature and pressure were raised to 80°C and 0.8 MPaG using an ethylene / hydrogen mixed gas with a hydrogen concentration of 0.45 vol%, and polymerization was carried out for 90 minutes. The resulting polymer was filtered and vacuum-dried at 80°C for 10 hours, yielding 8.17 g of ethylene-based polymer.
[0120] [Manufacturing Example 5] The same procedure as in Production Example 4 was carried out except that 5.0 mL of a toluene slurry of the solid catalyst component (X-5) was used instead of the toluene slurry of the solid catalyst component (X-4), to obtain 31.23 g of an ethylene polymer.
[0121] [Manufacturing Example 6] Production Example 4 was repeated except that 5.0 mL of a toluene slurry of the solid catalyst component (X-6) was used instead of the toluene slurry of the solid catalyst component (X-4), to obtain 18.33 g of an ethylene polymer.
[0122] [Example 1] A 1 L stainless steel autoclave equipped with a stirring blade and thoroughly purged with nitrogen was charged with 500 mL of heptane under a nitrogen atmosphere. Ethylene was then passed through to saturate the liquid and gas phases with ethylene. Next, 0.150 mmol of triisobutylaluminum, 1.5 mL of a 1 mg / mL toluene solution of dibutyl ether (Component (D)), and 5.0 mL of a toluene slurry of solid catalyst component (X-3) were added. The temperature and pressure were raised to 80 °C and 0.8 MPaG using ethylene gas, and polymerization was carried out for 90 minutes. The resulting polymer was filtered and vacuum dried at 80 °C for 10 hours, yielding 43.02 g of polyethylene.
[0123] [Example 2] The same procedure as in Example 1 was carried out except that the amount of the 1 mg / mL toluene solution of dibutyl ether added was changed to 2.5 mL, thereby obtaining 25.65 g of polyethylene.
[0124] [Example 3] A 1-L stainless steel autoclave equipped with a stirring blade and thoroughly purged with nitrogen was charged with 500 mL of heptane under a nitrogen atmosphere. Ethylene was then passed through the autoclave to saturate the liquid and gas phases with ethylene. Next, 1.0 mL of 1-hexene, 0.150 mmol of triisobutylaluminum, 2.5 mL of a 1 mg / mL toluene solution of dibutyl ether (Component (D)) and 5.0 mL of a toluene slurry of the solid catalyst component (X-6) were added. The temperature and pressure were raised to 80 °C and 0.8 MPaG using a 0.45 vol% hydrogen-containing ethylene / hydrogen gas mixture, and the polymerization reaction was carried out for 90 minutes. The resulting polymer was filtered and vacuum-dried at 80 °C for 10 hours, yielding 11.25 g of ethylene-based polymer.
[0125] [Method for measuring the ratio of the polymer derived from component (A) to the polymer derived from component (B)] In the above Production Examples and Working Examples, the quantitative ratio of the polymer derived from component (A) to the polymer derived from component (B) contained in the resulting polyethylene was determined by GPC peak separation as follows.
[0126] First, the molecular weight of the resulting polyethylene was measured by gel permeation chromatography (GPC). A gel permeation chromatograph, HLC-8321GPC / HT (Tosoh Corporation), was used as the liquid chromatograph. Two TSKgel GMH6-HT columns and two TSKgel GMH6-HTL columns (both with an inner diameter of 7.5 mm and a length of 30 cm) were used as separation columns. The column temperature was 140°C, and the mobile phase medium was orthodichlorobenzene (containing 0.025% dibutylhydroxytoluene). The mobile phase medium was moved at a rate of 1.0 mL / min. The sample concentration was 0.15 mg / mL, the sample injection volume was 0.4 mL, and a differential refractometer was used as the detector. The instrument was calibrated using monodisperse polystyrene (Tosoh Corporation). The relationship between retention time and signal intensity obtained by the measurement was recorded as a chromatogram.
[0127] The molecular weight distribution curve (G1) (hereinafter sometimes referred to as "(G1)") obtained from the chromatogram was compared with molecular weight distribution curves obtained by adding together, in various proportions, the molecular weight distribution curve (G2) (hereinafter sometimes referred to as "(G2)") of the component (A)-derived polymer and the molecular weight distribution curve (G3) (hereinafter sometimes referred to as "(G3)") of the component (B)-derived polymer. Here, the molecular weight distribution curve obtained for the polyethylene obtained in Production Example 1 was used as the molecular weight distribution curve (G2) of the component (A)-derived polymer, and the molecular weight distribution curve obtained for the polyethylene obtained in Production Example 2 was used as the molecular weight distribution curve (G3) of the component (B)-derived polymer.
[0128] Specifically, the comparison was carried out according to the following steps (S1) to (S5). (S1) For each of the numerical data (G1), (G2), and (G3), log (molecular weight) was divided into 0.02 intervals, and the intensity [d weight fraction / d log (molecular weight)] was normalized so that the area of the molecular weight distribution curve was 1.
[0129] (S2) For (G2), a constant a was added to all log(molecular weight) values, and all intensities were multiplied by an arbitrary factor x (x is a real number greater than or equal to 0) to obtain a first molecular weight distribution curve (G2'). Here, a was determined so that the log(molecular weight) of the rising edge on the high molecular weight side of (G1) and the log(molecular weight) of the rising edge on the high molecular weight side of (G2) matched. Furthermore, for (G3), a constant b was added to all log(molecular weight) values, and all intensities were multiplied by an arbitrary factor y (y is a real number greater than or equal to 0) to obtain a second molecular weight distribution curve (G3'). Here, b was determined so that the log(molecular weight) of the rising edge on the low molecular weight side of (G1) and the log(molecular weight) of the rising edge on the low molecular weight side of (G3) matched. The first molecular weight distribution curve (G2') and the second molecular weight distribution curve (G3') were then added together to obtain a composite molecular weight distribution curve (GS).
[0130] (S3) The difference in intensity at each log (molecular weight) was determined for the synthetic molecular weight distribution curve (GS) obtained in (G1) and (S2).
[0131] (S4) The difference obtained in (S3) was calculated for each of the multiple magnifications x and y while changing the magnifications x and y. When the absolute value of the difference obtained in (S3) was less than 0.04, it was determined that (G1) and the synthetic molecular weight distribution curve obtained in (S2) matched.
[0132] (S5) The magnifications x and y when it was determined that they matched were converted into mass % and used as the ratio of the amount of the polymer derived from component (A) to the amount of the polymer derived from component (B). From the comparison, The proportions of the polymer derived from component (A) and the polymer derived from component (B) contained in the polyethylene obtained in Production Example 3 were 7.2% by mass and 92.8% by mass, respectively. The proportions of the polymer derived from component (A) and the polymer derived from component (B) contained in the polyethylene obtained in Production Example 6 were 73.7% by mass and 26.3% by mass, respectively. The proportions of the polymer derived from component (A) and the polymer derived from component (B) contained in the polyethylene obtained in Example 1 were 9.4% by mass and 90.6% by mass, respectively. The proportions of the polymer derived from component (A) and the polymer derived from component (B) contained in the polyethylene obtained in Example 2 were 10.3% by mass and 89.7% by mass, respectively. The proportions of the polymer derived from component (A) and the polymer derived from component (B) contained in the polyethylene obtained in Example 3 were 80.6% by mass and 19.4% by mass, respectively. were calculated respectively.
[0133] The results of the above Production Examples and Examples are shown in Table 1. The relationship between the ratio of the component (A)-derived polymer to the component (B)-derived polymer obtained in Examples 1 and 2 and Production Example 3 and the amount of component (D) added is shown in Figure 1. The relationship between the ratio of the component (A-2)-derived polymer to the component (B-2)-derived polymer obtained in Example 3 and Production Example 6 and the amount of component (D) added is shown in Figure 2.
[0134] [Table 1]
[0135] A comparison of Production Example 3 with Examples 1 and 2, and a comparison of Production Example 6 with Example 3, reveals that as the amount of component (D) added increases, the proportion of polymer derived from component (B) contained in the resulting polyethylene decreases and the proportion of polymer derived from component (A) increases. In other words, the use of an additive can selectively deactivate component (B) and suppress the production of polymer from component (B).
Claims
1. A method for producing an olefin polymer, comprising a step of (co)polymerizing ethylene and one or more olefins selected from the group consisting of α-olefins having 3 to 20 carbon atoms in the presence of an olefin polymerization catalyst comprising the following components (A), (B), and (C): Component (A): a hafnium compound represented by the following general formula (1): 【Chemistry 1】 [In the general formula (1), n is a number that satisfies the valence of Hf, R 1 ~R 8 are each independently selected from the group consisting of a hydrogen atom, a hydrocarbon group, a halogen-containing group, an oxygen-containing group, a nitrogen-containing group, a boron-containing group, a sulfur-containing group, a phosphorus-containing group, a silicon-containing group, a germanium-containing group, and a tin-containing group, and may be the same or different from each other; R 1 ~R 8 two adjacent groups among Q 1 is a divalent group, which is a hydrocarbon group having 1 to 20 carbon atoms, a halogen-containing group, a silicon-containing group, a germanium-containing group, or a tin-containing group, and the hydrocarbon group having 1 to 20 carbon atoms may contain oxygen; X's each independently represent an atom or group selected from the group consisting of a hydrogen atom, a halogen atom, a hydrocarbon group, a halogen-containing hydrocarbon group, a silicon-containing group, an oxygen-containing group, a sulfur-containing group, a nitrogen-containing group, and a phosphorus-containing group, and may be the same or different. Component (B): a zirconium compound represented by the following general formula (2): 【Chemistry 2】 [In the general formula (2), n is a number that satisfies the valence of Zr, R 9 ~R 16 are each independently selected from the group consisting of a hydrogen atom, a hydrocarbon group, a halogen-containing group, an oxygen-containing group, a nitrogen-containing group, a boron-containing group, a sulfur-containing group, a phosphorus-containing group, a silicon-containing group, a germanium-containing group, and a tin-containing group, and may be the same or different from each other; R 9 ~R 16 two adjacent groups among Q 2 is a divalent group, which is a hydrocarbon group having 1 to 20 carbon atoms, a halogen-containing group, a silicon-containing group, a germanium-containing group, or a tin-containing group, and the hydrocarbon group having 1 to 20 carbon atoms may contain oxygen; X's each independently represent an atom or group selected from the group consisting of a hydrogen atom, a halogen atom, a hydrocarbon group, a halogen-containing hydrocarbon group, a silicon-containing group, an oxygen-containing group, a sulfur-containing group, a nitrogen-containing group, and a phosphorus-containing group, and may be the same or different. Component (C): at least one compound selected from the group consisting of organometallic compounds (c-1) represented by the following general formulas (3) to (5), organoaluminum oxy compounds (c-2), and compounds (c-3) that react with component (A) and component (B) to form an ion pair; R a m Al(OR b ) n H p X q ・・・(3) [In general formula (3), R a and R b each independently represents a hydrocarbon group having 1 to 15 carbon atoms, X represents a halogen atom, m is a number that satisfies 0<m≦3, n is a number that satisfies 0≦n<3, p is a number that satisfies 0≦p<3, and q is a number that satisfies 0≦q<3, and m+n+p+q=3. M a AlR a 4 ・・・(4) [In general formula (4), M a represents Li, Na or K, and R a represents a hydrocarbon group having 1 to 15 carbon atoms. R a r M b R b s X t ・・・(5) [In general formula (5), R a and R b each independently represents a hydrocarbon group having 1 to 15 carbon atoms; M b is selected from Mg, Zn, and Cd, X represents a halogen atom, r is 0<r≦2, s is 0≦s≦1, t is 0≦t≦1, and r+s+t=2. Component (D): a compound represented by the following general formula (6): R 17 -E-R 18 ・・・(6) [In the general formula (6), E represents an atom of Group 16 of the periodic table, and R 17 and R 18 each independently represents a hydrocarbon group having 1 to 20 carbon atoms.
2. 2. The method for producing an olefin polymer according to claim 1, wherein, in the general formula (6), E is an oxygen atom or a sulfur atom.
3. In the general formula (6), R 17 and R 18 and each independently represent an alkyl group having 1 to 20 carbon atoms,
4. In the general formula (6), R 17 and R 18 and each independently represent a linear alkyl group having 1 to 20 carbon atoms,
5. In the general formula (6), R 17 and R 18 The process for producing an olefin polymer according to any one of claims 1 to 4, wherein each of the groups is a linear alkyl group having 1 to 20 carbon atoms.
6. The method for producing an olefin polymer according to any one of claims 1 to 5, wherein the olefin polymerization catalyst is in a solid state.
7. The method for producing an olefin polymer according to claim 6, wherein the olefin polymerization catalyst further comprises a solid support (S).
8. 8. The process for producing an olefin polymer according to claim 7, wherein the component (C) is an organoaluminum oxy-compound, and the solid support (S) is a porous oxide.
9. The method for producing an olefin polymer according to any one of claims 1 to 8, wherein the component (A) is a hafnium compound represented by the following general formula (7), and the component (B) is a zirconium compound represented by the following general formula (8): 【Transformation 3】 [In the general formula (7), n is a number that satisfies the valence of Hf, R 19 ~R 30 are each independently selected from the group consisting of a hydrogen atom, a hydrocarbon group, a halogen-containing group, an oxygen-containing group, a nitrogen-containing group, a boron-containing group, a sulfur-containing group, a phosphorus-containing group, a silicon-containing group, a germanium-containing group, and a tin-containing group, and may be the same or different from each other; R 19 ~R 30 two adjacent groups among Q 1 is a divalent group, which is a hydrocarbon group having 1 to 20 carbon atoms, a halogen-containing group, a silicon-containing group, a germanium-containing group, or a tin-containing group, and the hydrocarbon group having 1 to 20 carbon atoms may contain oxygen; X's each independently represent an atom or group selected from the group consisting of a hydrogen atom, a halogen atom, a hydrocarbon group, a halogen-containing hydrocarbon group, a silicon-containing group, an oxygen-containing group, a sulfur-containing group, a nitrogen-containing group, and a phosphorus-containing group, and may be the same or different. 【Chemistry 4】 [In the general formula (8), n is a number that satisfies the valence of Zr, R 31 ~R 42 are each independently selected from the group consisting of a hydrogen atom, a hydrocarbon group, a halogen-containing group, an oxygen-containing group, a nitrogen-containing group, a boron-containing group, a sulfur-containing group, a phosphorus-containing group, a silicon-containing group, a germanium-containing group, and a tin-containing group, and may be the same or different from each other; R 31 ~R 42 two adjacent groups among Q 2 is a divalent group, which is a hydrocarbon group having 1 to 20 carbon atoms, a halogen-containing group, a silicon-containing group, a germanium-containing group, or a tin-containing group, and the hydrocarbon group having 1 to 20 carbon atoms may contain oxygen; X's each independently represent an atom or group selected from the group consisting of a hydrogen atom, a halogen atom, a hydrocarbon group, a halogen-containing hydrocarbon group, a silicon-containing group, an oxygen-containing group, a sulfur-containing group, a nitrogen-containing group, and a phosphorus-containing group, and may be the same or different.